Supply Chain Management Concepts Applied in the Oil & Gas Industry – A review of literature - Adel Alhosani; Safie Mohamed Zabri; Fareed Aljaberi; Ali Almansoori (International Journal of Supply Chain Management, 2019)
The recent trends in the oil gas has shown volatility in this market and the low oil prices has influenced this industry in a big way. The researchers and practitioners in this field have realized the importance of efficient Supply Chain Management (SCM) to have competitive edge in this industry. The dynamic nature of the supply as well as the demand has contributed to the unique challenges in managing the supply chain in this sector. The main objective of this study is to understand the application of different SCM concepts in the Oil and Gas industry. The study involved the systematic literature review of the various articles published by prominent researchers in this field in reputed journals and databases like Scopus, Web of Science (WOS). The findings have identified 52 different models of SCM which are used in the oil gas industry. This study is a contribution to the body of knowledge regarding the use of SCM concepts in oil and gas industry. Future studies can use this as a reference to understand the existing SCM concept in this industry and base their empirical study the suitability and influence of these concepts on the efficient supply chain management in Oil gas industry.